Poly(Lactic-co-glycolic) Acid and Phospholipids Hybrid Nanoparticles for Regeneration of Biological Tissue - Antonio Minó; Giuseppe Cinelli; Gianluca Paventi; Gianluca Testa; Fabiana Passaro; Francesco Lopez; Luigi Ambrosone (ChemEngineering, 2022)
In tissue regeneration, biomaterials facilitate biological processes. However, a treatment with biomaterials will be successful only if supported by simple and inexpensive technologies which stimulate the regenerative processes. The present study focused on the possibility of creating formulations from which then to obtain suitable materials for the regeneration of heart tissue. The experimental procedure for precipitation of polymer- nanoparticles was modified ad hoc to obtain hybrid poly lactic-co-glycolic acid (PLGA)-phospholipid nanoparticles. The properties of the formulations produced by direct PLGA-phospholipid co-precipitation depend on the mass ratio <semantics>R=</semantics> polymer mass/phospholipid mass. The value of this parameter allows us to modulate the properties of the formulations. Formulations with <semantics>R</semantics> = 1.5, 2.3, 4, and 9 were prepared, and for each of them the particle-size distribution obtained by dynamic light scattering was studied. All samples showed that the hydrodynamic diameter decreases with increasing <semantics>R</semantics> value. This behavior is interpreted as polymer coil shrinkage due to contacts with the non-solvent. The spreadability and ease of obtaining thin sheets were evaluated for each formulation. The formulation with <semantics>R=4</semantics> resulted in a homogeneous and easily workable material in thin sheets.